Pengaruh Perbandingan Tepung Sukun (Artocarpus altilis) dan Terigu terhadap Karakteristik Donat - Dorothy Sabatini, Sazkya; Yusa, I Made; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
This study aims to determine the effect of comparison of breadfruit flour and wheat on the characteristics of donuts and to determine the right comparison of breadfruit flour and wheat to produce donuts with the best characteristics. The experimental design used was a Completely Randomized Design (CRD) with the comparison of breadfruit flour and wheat consisting of 5 levels namely 10%:90%, 20%:80%, 30%:70%, 40%:60%, 50%:50%. The treatment was repeated 3 times in order to obtain 15 experimental units. The data obtained were analyzed by Analysis of Variance (ANOVA) and if the treatment had a significant effect then it was continued by the Duncan’s Multiple Range Test (DMRT). The comparison of breadfruit flour and wheat had a significant effect on water content, ash content, crude fiber content, swelling power, color, aroma, texture, taste, and overall acceptance. The comparison of 10% of breadfruit flour and 90% of wheat produced donuts with the best characteristics with 20.81% of water content, 1.33% of ash content, 7.86% of crude fiber content, 38.33% of swelling power, the color was liked, the aroma was rather typical of breadfruit and liked, the texture was slightly soft and rather liked, the taste was rather liked, and the overall acceptance was rather liked.